Imersões em espaços de Einstein: aplicações a relatividade geral - Cruz, Flávio França (2007)
In this work, we present some results on the existence of local immersions in Einstein spaces, obtained by Carlos Romero and collaborators and published in [1], [4] and [6]. In fact, research developed by these authors allowed obtaining even more comprehensive results than those presented at present.